2021
DOI: 10.3390/app11188543
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Laboratory Scanner Versus Intra-Oral Scanner on Determining the Implant Axis by Using Three Different Scan Abutments

Abstract: Background: The purpose of this in vitro study was to compare the implant axis’ spatial position and orientation by using laboratory scanner versus intra-oral scanner with three different scan abutments. Methods: A 3D model was printed with an internal hex implant analog in the place of teeth 35#. Three standard scan abutments were used: MIS (two-piece titanium), AB (two-piece PEEK and titanium base) and ZZ (one-piece PEEK). Each scan abutment was scanned 30 times by TRIOS E3 (laboratory scanner) and 30 times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…We assume that because of the cylindrical shape of the ZZ ISB, it is easier to define and superimpose the axis. As for this point, in our previous study for a single ZZ ISB, it was found that one piece with a cylindrical shape had the lowest intra-implant angle (0.4 mm) compared to two other ISBs (MIS and AB) [29].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We assume that because of the cylindrical shape of the ZZ ISB, it is easier to define and superimpose the axis. As for this point, in our previous study for a single ZZ ISB, it was found that one piece with a cylindrical shape had the lowest intra-implant angle (0.4 mm) compared to two other ISBs (MIS and AB) [29].…”
Section: Discussionmentioning
confidence: 82%
“…It is already known from the literature that the geometry of the scan abutments, onepiece or two pieces, the materials, and the scanning techniques are some of the parameters that may affect the accuracy [15,30], In the current study, we decided to use only the titanium ISB as we realized in our previous research that PEEK is less accurate and we recommended the use of titanium [29]. Pan et al tested two different scan abutments and their impact on accuracy.…”
Section: Discussionmentioning
confidence: 99%